HYPOCRISY IN NARAYAN’S THE GUIDE - Frendly N. W Wantah; Tini Mogea; Olga Rorintulus (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2021)
This study is conducted to reveal the hypocrisy and explain its causes and effects as seen in Narayan’s The Guide. The writers delimit this study on revealing hypocrisy in the novel itself. Particularly, this study delimit to hypocritical actions and words of Raju as experienced throughout the story. In carrying out this research, the data are got from the novel by Narayan entitled The Guide as primary source and also supported by other relevant references such as books, documents and web sources about hypocrisy are considered as secondary. In doing the data analysis, the researchers use objective approach and show about the hypocrisy and its causes and effects in the novel. The result shows that a hypocrite is a person who is illustrated as someone who has no principles and is inconsistent. They have in mind how they can benefit from what they are doing. Raju when talking to people always confirms what he says. He always covers his character by always being polite and even exaggerated at times. He always had a sweet mouth and sometimes pretended to support what people said. It is often easy to praise anyone. The causes of Raju’s hypocrisy is targeting material profit and obtaining self-pleasure. The impact of Raju’s hypocrisy is the decrease of moral.